Study and Analysis of Shape of Electrode Implemented in Supercapacitor with Focus on Design and Fabrication for Application in Load - Prof. Mugdha P. Bhajekar; Ojesh Patil; Sanket Mahajan; Vaishnavi Chirmade; Sohan Dalvi (International Journal of Engineering and Management Research, 2023)
Electric energy storage is an essential issue in the modern world. Various sorts of research on batteries and supercapacitors are now underway. Supercapacitor is an alternate energy storage device with a high power density and specific capacitance. A supercapacitor is a device that stores electric energy as an electrostatic field. We show a model of an asymmetric supercapacitor built using an anode of activated carbon + manganese dioxide coating on a stainless-steel gauge and a cathode of pure activated carbon coating. Also incorporated with the polyethylene separator. The supercapacitor's energy storage is controlled through modifying the spacing across the two electrodes and the physical shape of the electrodes. We tried four different electrode shapes: square, rectangle, triangle, and semicircle. It has been observed that modifying the shape of the electrode had an effect on most of the parameters. This can be achieved by experimenting with the actual configuration by changing the shape of electrodes in a supercapacitor. This provides excellent results and graphs displaying the maximum capacitance of supercapacitor with rectangular electrode designs.